Insulin-Like Growth Factor-I Might be a Predictor for Severe Non-Alcoholic Fatty Liver Disease in Morbidly Obese Patients - Turgut, Seda; Acarer, Didem; Seyit, Hakan; Pamuk, Naim; Piskinpasa, Hamide; Bozkur, Evin; Karabulut, Mehmet; Cakir, Ilkay (Hormone and Metabolic Research, 2022)
The aim of the study was to compare the IGF-1 levels, metabolic and clinical parameters among the ultrasonographically classified non-alcoholic fatty liver disease (NAFLD) groups and determine the factors that may predict the NAFLD severity in patients with morbid obesity. This study was conducted on 316 morbidly obese patients (250 F/66 M). The data of patients before and 1st-year after bariatric surgery were recorded. According to the ultrasonographically NAFLD screening, patients with normal hepatic features were classified as Group 1(n=57), with mild and moderate NAFLD were classified as Group 2(n=219), and with severe NAFLD were classified as Group 3(n=40). IGF-1 standard deviation scores (SDSIGF1) were calculated according to age and gender. Parameters that could predict the presence and severity of NAFLD were evaluated. IGF-1 levels were significantly associated with Group 3 than Group 1(p=0.037), and the significance remained between the same groups when IGF-1 levels were standardized as SDSIGF1(p=0.036). Decreased levels of SDSIGF1 explained 5% of severe NAFLD than the normal group (p=0.036). Liver Diameter, FPG, ALT, AST, and GGT were also found as significant predictors for severe NAFLD. There were significant differences between pre-and postop values in all groups (p<0.001). This study showed that IGF-1 might be considered a sgnificant predictor of severe NAFLD in morbidly obese patients. It is crucial in clinical practice to determine predictive factors of NAFLD that could support the diagnosis accompanied by non-invasive imaging methods.